Cover Image. (17th August 2018) - Masoomi, Kianoosh; Ghiaci, Mehran; Botelho do Rego, A.M.
Abstract : The cover image, by Kianoosh Masoomi et al., is based on the Full Paper Selective vapor‐phase oxidation of o‐xylene to phthalic anhydride over Co‐Mn/H3 PW12 O40 @TiO2 using molecular oxygen as a green oxidant, https://doi.org/10.1002/aoc.4461 .